2009
DOI: 10.1073/pnas.0813348106
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 gene silencing with siRNA suppresses ovarian tumor growth and metastasis

Abstract: Claudin-3 (CLDN3) is a tight junction protein that is overexpressed in 90% of ovarian tumors. Previous in vitro studies have indicated that CLDN3 overexpression promotes the migration, invasion, and survival of ovarian cancer cells. Here, we investigated the efficacy of lipidoid-formulated CLDN3 siRNA in 3 different ovarian cancer models. Intratumoral injection of lipidoid/CLDN3 siRNA into OVCAR-3 xenografts resulted in dramatic silencing of CLDN3, significant reduction in cell proliferation, reduction in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 17 publications
5
78
0
Order By: Relevance
“…Cell culture, transfection, and viability assay A2780 cells (T. (22), were authenticated and maintained as described previously (23). Frozen aliquots of cells were prepared upon receipt.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture, transfection, and viability assay A2780 cells (T. (22), were authenticated and maintained as described previously (23). Frozen aliquots of cells were prepared upon receipt.…”
Section: Methodsmentioning
confidence: 99%
“…Its overexpression has been identified relating to migration, invasion and proliferation of cancer cells (16,19,35). Interestingly, CLDN3 is identified as one of the only two claudin family members capable of mediating cpe binding and cytolysis (36).…”
Section: Discussionmentioning
confidence: 99%
“…According to shrnA design principles and published sirnA sequences for clDn3, shrnA primers targeting clDn3 (sense 5'-tcccgcAAcAtcAtcAcgtcgcAttcAAgAcgtg cgAcgt gAt gAt gt t g c t t t t t t g -3' a nt is ens e, 5'-AgctcAAAAAAgcAAcAtcAtcAcgtcgcAcgt cttgAAtgcgAcgtgAtgAtgttgc-3') were designed and chemically synthesized for plasmid construction (19). the HK sequence, which has no homology with any known mammalian gene sequences, was used as the negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cationic and neutral lipoplexes have exhibited good efficacy with different toxicity and protein adsorption. [11][12][13][14][15] Previously, we also reported that lipoplexes of siRNA constructed with trimethyl[2,3-(dioleoxy)-prolyl] ammonium chloride and cholesteryl 3β-N-(dimethylaminoethyl) carbamate hydrochloride showed a significant silencing effect in a mouse colon carcinoma cell line expressing luciferase regularly. 16) On the other hand, cationic polymers are one of the most popular non-viral gene vectors due to their excellent ability to compact anionic genes, synthetic controllability, better flexibility achieved simply by varying the chemical composition, molecular weight (MW), and architecture (linear, randomly branched, dendrimer, block, and graft copolymer).…”
mentioning
confidence: 99%